Performance of bottom ash treated peat soil in improving bearing capacity - Sonia Singgar, Lembang (2018)
Peat soil with low shear strength, high compressibility and high initial water content, is deem unsuitable for construction process. Hence soil mixing with Ordinary Portland Cement (OPC) is one of the methods commonly used to treating the peat soil.However due to high cost this method is still not the best method recommended for this purpose. In power plant industry bottom ash considered waste material with nowhere to dispose and no reuse value. Previous research shows bottom ash mix with cementpowder is expected to stabilise the peat soil by changing it natural properties. This research aims to study the bearing capacity and group index of stabilized tropical peat soil of East Coast of Peninsular Malaysia by mixing same proportion of OPC cement and various proportion of bottom ash. Also this study will discuss the behaviour of peat soil with or without the bottom ash and cement stabilization. A fixed proportion of OPC binders and various proportion of bottom ash (pozzolanic material) in a series of laboratory test were conducted. All samples have undergone 3 days soaked in water experience for soaked sample. Unsoaked sample was tested after mixing. The improvement in bearing capacity was being evaluated using California Bearing Ratio (CBR) test. The results shows that after mixing with bottom ash the bearing capacity of peat soil increase with increase the bottom ash percentage in peat soil.